Synthesis and Performance of Nickel/Reduced Graphene Oxide Hybrid for Hydrogen Evolution Reaction - Franceschini, Esteban Andrés (2018)
In this work, a simple and reproducible method for the syntheses of hybrid nickel/reduced graphene oxide electrodes is presented. This method consists in a direct modification of a conventional nickel electrodeposition bath, making the synthesis industrially scalable. The synthesized catalyst is structural and electrochemically characterized and compared to the traditional electrodeposited nickel. The kinetics of hydrogen evolution reaction (HER) is studied on both conventional nickel watts (Ni-watts) and nickel/reduced graphene oxide hybrid (NirGO). An increment in the catalytic activity is observed along with the absence of nickel hydrides. Thus, the NirGO catalyst presents a higher catalytic activity towards HER, and the presence of graphene in the Ni matrix inhibits the nickel hidruration. [Figure not available: see fulltext.].